Tugas Dan Tanggung Jawab Guru Pendidikan Agama Kristen Dalam Menangani Psikologi Anak Akibat Pandemi Covid-19 - Imayanti Nainggolan; Talizaro Tafonao (Sekolah Tinggi Teologi Syalom Bandar Lampung, 2021)
This article is a theoretical study of the duties and responsibilities of Christian religious education teachers as educators who are able to teach, guide and even direct students during the Covid-19 pandemic. The importance of Christian religious education teachers during the pandemic, not only teaching or transferring knowledge. However, the duties and responsibilities of Christian religious education teachers during a pandemic are to handle the negative psychology of students and help and lead children to know the real love of God in the Lord Jesus Christ. The duties and responsibilities of Christian religious education teachers during the pandemic are, as teachers as motivators so that children get assistance to find solutions by providing direction or advice based on the truth of God's Word, even increasing children's spirituality, growing their faith and hope in God. Christian religious education teachers must also provide assistance, care, and sincere love, so that students or children feel valued and have enthusiasm. In addition to Christian religious education teachers as motivators, also Christian religious education teachers as innovators, as evaluators, giving themselves to their students, even Christian religious education teachers are able to bring students to life changes for children who experience negative psychology. To achieve what the author's goal is, the author uses a qualitative method of literature review, namely by collecting data and information related to the problem under study through books, magazines, manuscripts, and supported by several references. online for the completion of this paper.